Study Tutors' Performance at the Sanggar Kegiatan Belajar (SKB) in East Java, Indonesia: The Impact of Welfare, Resilience, and Work Motivation - Avrilianda, Decky; Shofwan, Imam; Arina Rahma, Rezka (Universitas Negeri Semarang, 2025)
The aim of this research is to examine how work motivation, resilience, and welfare affect the performance of tutors pursuing SKB in East Java. The study involved 119 civil servants in East Java, with a sample size of 54 determined using the Slovin formula. The findings indicate that: (1) The welfare variable had a t-count of 3.946 and a significance value of 0.000, showing a partial significant impact on performance. (2) The resilience variable had a t-value of 2.792 and a significance value of 0.011, also indicating a partial impact on performance. (3) Work motivation had a t-value of 2.455 and a significance value of 0.035, suggesting a partially significant effect on performance. Overall, the performance of tutors is significantly influenced by welfare, resilience, and work motivation.